Early Diagnosis And Integrated Management Of Peritoneal Cancer-The Main Role Of Pharmacists, Radiologists, Nursing, Administrators, And Other Healthcare Professionals-An Updated Review (The Review of Diabetic Studies, 2024)
Background: Peritoneal surface malignancy represents a heterogeneous group of primary and secondary cancers involving the serosal lining of the abdominal cavity, characterized by late presentation, diffuse spread, and high morbidity.Aim: This review aimed to comprehensively evaluate the role of integrated multidisciplinary management in peritoneal cancer, emphasizing early diagnosis, therapeutic strategies, and the essential contribution of healthcare professionals in optimizing outcomes.Methods: A narrative literature review approach was undertaken using published studies, clinical guidelines, and recent evidence addressing epidemiology, pathophysiology, diagnostic modalities, and multimodal treatment approaches. Results: The findings demonstrate that peritoneal cancer is most commonly diagnosed at advanced stages due to nonspecific clinical presentation and limited early detection tools. Imaging modalities such as CT, MRI, and PET-CT play a central role in staging and disease assessment, while cytology, immunohistochemistry, and laparoscopy remain essential for definitive diagnosis. Management has evolved significantly with the development of cytoreductive surgery combined with intraperitoneal chemotherapy, particularly HIPEC, EPIC, and emerging approaches such as PIPAC and bidirectional chemotherapy. Evidence indicates improved survival outcomes in selected patients undergoing multimodal treatment compared with conventional palliative care. The review highlights that optimal management requires coordinated involvement of pharmacists, radiologists, nurses, surgeons, and healthcare administrators to ensure timely diagnosis, safe chemotherapy delivery, perioperative care, and treatment coordination.Conclusion: The study concludes that multidisciplinary integration is fundamental to improving survival, reducing complications, and enhancing quality of life in patients with peritoneal malignancies.